Determinación de los factores que inciden en la disolución y liquidación de las compañías por sector económico de la provincia de Loja periodo 2015-2020 - Montaño Montaño, Martha Lucía (2022)
The present research is about: “THE DETERMINATION OF FACTORS THAT AFFECT THE DISOLUTION AND SETTLEMENT OF COMPANIES IN ECONOMIC AREA IN THE PROVINCE OF LOJA DURING THE PERIOD 2015-2020” it developed with the main objective to know the different factors that index the dissolution and settlement of companies in the economic area in the province of Loja in period 2015-2020. For the development of this present thesis the following objectives were done; checked the companies information that come in the process of dissolution and settlement in the economic area in the province of Loja in 2015-2020 period; to collect information of the companies that came in in the process of dissolution and settlement by the economic area and built the data base of the companies that came in the process of dissolution and settlement according to the economic area depending on the main indicators. The methodological process of review, collection and elaboration of the data base with the economical and financial data base of companies that came in the process of dissolution and settlement in the province, supported with the scientific investigation. To concluded that the information of SUPERCIAS, the economic areas more affected with the dissolution and settlement by the resolution of the main regulatory body in the Construction, Business wholesale and retail trade, transport and packing; and its recommended that the companies that came in the process already mention must applied the financial indicators in a periodic way to take decisions on time.